Combining sinus plain film and sinus ultrasound as a screening tool for maxillary fungal sinusitis. Issue 3 (8th March 2022) - Ho, Nien-Hsuan; Hung, Li-Ting; Kuan, Edward C.; Ho, Ching-Yin; Hsu, Cheng-Chieh; Lan, Ming-Ying
Abstract : Background: Early identification of fungal sinusitis remains a challenge. Previously, we observed a high false negative rate of using A-mode ultrasound to diagnose maxillary fungal sinusitis. This study aims to assess the accuracy of the diagnosis of fungal maxillary sinusitis using sinus plain film and ultrasound. Methods: The screening criteria is defined as the combination of a positive sinus plain film and a false negative sinus ultrasound. We retrospectively reviewed preoperative imaging of patients with fungal sinusitis and unilateral bacterial sinusitis of the maxillary sinus undergoing functional endoscopic sinus surgery from May 2013 to December 2019 in our hospital and evaluated the diagnostic performance of this screening method. Results: Forty-eight patients were included. Twenty-two and 26 patients were diagnosed with fungal sinusitis and bacterial sinusitis, respectively. Sixteen patients (72.7%) with fungal sinusitis presented with a false negative sinus ultrasound and met our screening criteria for fungal sinusitis. The screening criteria reached significance in the receiver operating characteristic curve analysis ( p < 0.001). The area under the curve was 0.829. The sensitivity, specificity, and accuracy are 72.7%, 93.2%, and 88.4%, respectively. Conclusion: A high false negative rate of sinus ultrasound in patients with fungal sinusitis was found. A positive sinus plain film combined with a false negative sinus ultrasound can potentially become an easy and cost-effective screening tool for diagnosing fungal maxillary sinusitis before consideration of computed tomography scanning.